2010
DOI: 10.1105/tpc.109.073072
|View full text |Cite
|
Sign up to set email alerts
|

MOTHER OF FT AND TFL1Regulates Seed Germination through a Negative Feedback Loop Modulating ABA Signaling inArabidopsis   

Abstract: Abscisic acid (ABA) and gibberellin (GA) are two antagonistic phytohormones that regulate seed germination in response to biotic and abiotic environmental stresses. We demonstrate here that MOTHER OF FT AND TFL1 (MFT), which encodes a phosphatidylethanolamine-binding protein, regulates seed germination via the ABA and GA signaling pathways in Arabidopsis thaliana. MFT is specifically induced in the radical-hypocotyl transition zone of the embryo in response to ABA, and mft loss-of-function mutants show hyperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
293
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 302 publications
(319 citation statements)
references
References 60 publications
(100 reference statements)
18
293
0
2
Order By: Relevance
“…GUS staining of MFT(P2)-GUS plants 9 showed that MFT was highly expressed in mature pollen grains in stamens (Fig. 2B) and in the endosperm of mature ovules (Fig.…”
Section: Mft Is Expressed In Gametophytes and Developing Seedsmentioning
confidence: 99%
See 4 more Smart Citations
“…GUS staining of MFT(P2)-GUS plants 9 showed that MFT was highly expressed in mature pollen grains in stamens (Fig. 2B) and in the endosperm of mature ovules (Fig.…”
Section: Mft Is Expressed In Gametophytes and Developing Seedsmentioning
confidence: 99%
“…2C). We have recently shown that MFT is highly expressed in developing seeds by quantitative real-time PCR, 9 but the precise localization of MFT in developing seeds has not been examined. We thus performed in situ hybridization to examine MFT expression in further investigated whether MFT is also involved in the crosstalk between ABA and BR.…”
Section: Mft Is Expressed In Gametophytes and Developing Seedsmentioning
confidence: 99%
See 3 more Smart Citations